Age independent survival benefit for patients with small hepatocellular carcinoma undergoing percutaneous cryoablation: A propensity scores matching study - Zhang, Huixin; Xu, Muoyan; Shao, Jiashen; Kong, Huifang; Gao, Xudong; Zhang, Wei; Chang, Xiujuan; Yang, Bin; Chen, Yan; Dong, Zheng; Huang, Jiagan; Zeng, Zhen; et al. (Frontiers in Oncology, 2023)
Background: Hepatocellular carcinoma (HCC) is the major cause of malignancy-related deaths worldwide, and its incidence is likely to increase in the future as life expectancy increases. Therefore, the management of elderly patients with HCC has become a global issue. Aim of this study was to assess whether elderly patients with small HCC could obtain survival benefit from cryoablation (CRYO) in a real-world. Materials and methods: From July 2007 to June 2013, 185 patients with small HCC who underwent curative-intent percutaneous CRYO. All patients were divided into three groups according to age distribution. Overall survival (OS) and tumor-free survival (TFS) were compared between among of groups before and after the 1:1 propensity score matching, respectively. Univariate and multivariate Cox analyses were performed to determine the potential relationships between variables and prognostic outcomes. Results: One hundred and eighty-five patients (144 men, 41 women) received CRYO for small HCC, including 59 patients with age <50 years, 105 patients with age between 50 and 65 years, and 21 patients with age >65 years. The three age groups showed significant differences in the terms of underlying chronic liver disease and the number of patients with minor postoperative complications. After propensity score matching, the younger and elderly groups showed significant differences in mean OS (P=0.008) and tumor progression (P=0.050). However, no significant differences were shown in mean PFS (P=0.303). The Cox multivariate analysis showed that the Child-Pugh grade (HR=3.1, P<0.001), albumin (HR=0.85, P=0.004) and total of bilirubin (HR=1, P=0.024) were the independent prognostic factor for mean OS. Conclusion: Our propensity-score-matched study suggested that elderly patients with small HCC can achieve acceptable prognostic outcomes with PFS similar to those of younger patients with small HCC after treatment with CRYO, while Child-Pugh grade, bilirubin and serum albumin levels were associated with the prognosis of small HCCs.